Supporting students’ social-emotional learning in Indonesian primary schools - Rahmawati, Dini (2019)
The large amounts of time children spend in school every day put schools in a role of significant influence in not only a student’s academic achievement but also the conceptualization of their social and emotional being. Schools provide support in social-emotional learning (SEL) through a variety of ways such as through teacher-student interaction, curriculum design, and a network of school-based support. In Indonesia, character education is integrated into the national curriculum to provide guidance for teachers, schools, and communities in developing students’ social and emotional skills. Using CASEL’s five competencies of SEL as a framework, this qualitative study aims to explore the various forms of SEL support teachers and schools provide for primary school students in Indonesia. This study utilizes teacher interviews and classroom observations using a case study research design to examine the application of SEL both in the classroom and school. The findings of this study suggest that teachers and schools have demonstrated efforts to support the SEL competencies through various forms of support in attempt to reinforce students’ social and emotional development. However, the observed practices were insufficient in supporting CASEL’s model of SEL. In this case, cultural factors need to be considered when contextualizing these results. Thus, future studies on the effects of SEL interventions on students as well as further development of SEL practices in schools are recommended.